A potential pathway for managing diabetic patients with arterial emboli detected by retinal screening. - Hadley, G; Earnshaw, J; Stratton, I; Sykes, J; Scanlon, P (2011)
OBJECTIVE: The aim was to review a pathway of care for diabetic patients found to have retinal artery emboli detected by retinal screening. DESIGN: This was a retrospective review of a pathway agreed in 2001 by a multidisciplinary team. MATERIALS AND METHODS: The prospectively collected Gloucestershire Diabetic Retinal Screening Programme database was reviewed; patients sent for carotid duplex imaging underwent review of their scan results and their casenotes. RESULTS: The prevalence of retinal emboli was 214 out of 25,299 diabetic patients who had retinal screening (0.85%). Some 200 diabetic patients underwent carotid duplex imaging; 23 had ipsilateral and 2 had contralateral carotid stenosis > 70%. Of these, ten patients underwent carotid endarterectomy without any major morbidity. CONCLUSIONS: [corrected] A pathway was established for the small number of patients with retinal emboli, and could be tested in other populations.